A prospective evaluation of thiamine and magnesium status in relation to clinicopathological characteristics and 1-year mortality in patients with alcohol withdrawal syndrome - Donogh Maguire; Dinesh Talwar; Alana Burns; Anthony Catchpole; Fiona Stefanowicz; Gordon Robson; David P. Ross; David Young; Alastair Ireland; Ewan Forrest; Peter Galloway; Michael Adamson; et al. (Journal of Translational Medicine, 2019)
Abstract Background Alcohol withdrawal syndrome (AWS) is routinely treated with B-vitamins. However, the relationship between thiamine status and outcome is rarely examined. The aim of the present study was to examine the relationship between thiamine and magnesium status in patients with AWS. Methods Patients (n = 127) presenting to the Emergency Department with AWS were recruited to a prospective observational study. Blood samples were drawn to measure whole blood thiamine diphosphate (TDP) and serum magnesium concentrations. Routine biochemistry and haematology assays were also conducted. The Glasgow Modified Alcohol Withdrawal Score (GMAWS) measured severity of AWS. Seizure history and current medications were also recorded. Results The majority of patients (99%) had whole blood TDP concentration within/above the reference interval (275–675 ng/gHb) and had been prescribed thiamine (70%). In contrast, the majority of patients (60%) had low serum magnesium concentrations (< 0.75 mmol/L) and had not been prescribed magnesium (93%). The majority of patients (66%) had plasma lactate concentrations above 2.0 mmol/L. At 1 year, 13 patients with AWS had died giving a mortality rate of 11%. Male gender (p < 0.05), BMI < 20 kg/m2 (p < 0.01), GMAWS max ≥ 4 (p < 0.05), elevated plasma lactate (p < 0.01), low albumin (p < 0.05) and elevated serum CRP (p < 0.05) were associated with greater 1-year mortality. Also, low serum magnesium at time of recruitment to study and low serum magnesium at next admission were associated with higher 1-year mortality rates, (84% and 100% respectively; both p < 0.05). Conclusion The prevalence of low circulating thiamine concentrations were rare and it was regularly prescribed in patients with AWS. In contrast, low serum magnesium concentrations were common and not prescribed. Low serum magnesium was associated more severe AWS and increased 1-year mortality.